Incidence of endosymbiont bacteria Wolbachia in cowpea weevil Callosobruchus maculatus Fabricius (Coleoptera, Chrysomelidae). - Bilal Rasool; Tahira Younis; Saba Zafar; Aqsa Parvaiz; Zeeshan Javed; Inshaal Rasool; Muhammad Shakeel (PLoS ONE, 2024)
This study focuses on the cowpea weevil, Callosobruchus maculatus, a globally distributed grain pest that affects cereals and pulses. Using chemicals to store grains can harm pest control and pose risks to consumers and the environment. The facultative intracellular symbiont bacteria Wolbachia can affect host's reproductive capacities in a variety of ways, which makes it useful in the management of pests such as C. maculatus. The main goal of the study was to identify Wolbachia diversity in the C. maculatus population. Phylogenetic analysis utilized mitochondrial COI and 12S rRNA genes to identify the host C. maculatus, while screening for Wolbachia was conducted using genes (wsp, coxA, and ftsZ) genes. Molecular phylogenetic analysis of the Wolbachia genes resulted in one new Wolbachia strain (wCmac1) in C. maculatus populations and contrasting already published data of other Callosobruchus strains. The study discussed the detection of Wolbachia and its phylogenetic comparison with other C. maculatus and Coleopteran populations. It is important to take these findings into account when considering host-pathogen interactions.